Chemical and microbiological farm milk quality determination in three Croatian regions - Neven Antunac; Jasna Đermadi; Miljenko Konjačić; Rajka Božanić; Zoran Bašić; Vera Volarić (Mljekarstvo)
The purpose of this study was to determine chemical and microbiological quality of raw milk from 30 farms of different sizes from eastern, central and southern Croatian regions. Samples of fresh raw milk (n=360) are determined by the content of fat, protein, total solids, and the number of microorganisms and somatic cells. Analysed milk derived from Holstein, Simmental and Brown Swiss cows, and their crossbred. Chemical composition of milk was determined by infrared spectrophotometry, microbiological quality by milk epifluorescence flow cytometry, and the number of somatic cells in milk was determined by fluoro-opto-electronic method. The results of chemical quality of milk - of milk fat and protein entirely, for all groups of large and small farms in eastern, central and southern regions meet the requirements of the “Regulations on the Quality of Fresh Raw Milk”. Looking at the value of the total number of microorganisms, only a group of small agricultural holdings of the southern region do not meet the requirements prescribed by the Regulations on the Quality of Fresh Raw Milk in 2000. Small agricultural holdings of the southern region had significantly higher total number of microorganisms (P<0.0001) in relation to the other two groups. There was a statistically significant difference (P<0.01) between somatic cell count (SCC) in milk of all three region’s large agricultural holdings, while the SCC in milk of small agricultural holdings of different regions did not show statistically significant difference (P<0.05).